A self-healing and mutual-healing key distribution scheme using bilinear pairings for wireless networks - Tian, Biming; Han, Song; Dillon, Tharam S. (Institute of Electrical and Electronics Engineers (IEEE) Computer Society, 2008)
Self-healing key distribution mechanism can be used to establish session keys within a large and dynamic groups of users over an unreliable wireless network. Mutual-healing key distribution mechanism deals with some deficiency existed in self-healing key distribution mechanism. It is a complementarity to the self-healing mechanism. In this paper, a self-healing key distribution scheme using bilinear pairings is proposed. As far as we know, it is the first self-healing and mutual-healing key distribution scheme based on bilinear pairings. The contributions of this paper are as follows: firstly, the scheme is collusion-free for any coalition of non-authorized users. Secondly, the private key has nothingto do with the number of revoked users and can be reused as long as it is not disclosed. Thirdly, the storage overhead for each user is a constant. In addition, we present technique details on how to realize mutual-healing.